Probing the non-thermal emission geometry of AR Sco via optical phase-resolved polarimetry. Issue 2 (11th December 2021) - du Plessis, Louis; Venter, Christo; Wadiasingh, Zorawar; Harding, Alice K; Buckley, David A H; Potter, Stephen B; Meintjes, P J
ABSTRACT: AR Sco is a binary system that contains a white and red dwarf. The rotation rate of the white dwarf (WD) has been observed to slow down, analogous to rotation-powered radio pulsars; it has thus been dubbed a 'white dwarf pulsar'. We previously fit the traditional radio pulsar rotating vector model to the linearly polarized optical data from this source, constraining the system geometry as well as the WD mass. Using a much more extensive data set, we now explore the application of the same model to binary phase-resolved optical polarimetric data, thought to be the result of non-thermal synchrotron radiation, and derive the magnetic inclination angle α and the observer angle ζ at different orbital phases. We obtain an ∼10° variation in α and ∼30° variation in ζ over the orbital period. The variation patterns in these two parameters is robust, regardless of the binning and epoch of data used. We speculate that the observer is detecting radiation from an asymmetric emission region that is a stable structure over several orbital periods. The success of this simple model lastly implies that the pitch angles of the particles are small and the pulsed, non-thermal emission originates relatively close to the WD surface.